The Implementation of Guidance and Counseling Services at Islamic Senior High School - Hidayat, A Taufiq; Purwanto, Edy; Awalya, Awalya (Jurnal Bimbingan Konseling, 2023)
Any guidance and counseling services at school will affect students’ development. Thus, all counseling programs at school must be in line with the school vision and missions to emerge innovations in problem-solving so that finally the counseling programs can result changes in students’ behavior and obtain public trust for the school. Regarding this background, the present study attempted to describe the implementation of guidance and counseling services at a senior high school level. It was a qualitative study which involved 9 subjects, namely one school counselor, a school principal, two subject teachers, two guardians, and three students selected using snowball and purposive sampling techniques. Their data were collected using interviews and analyzed using an interactive qualitative model, covering data collection, data reduction, data presentation, and conclusion drawing. The results were 1) the guidance and counseling model implemented at the Islamic senior high school was focused on Islamic counseling which emphasized religious aspects in its services, 2) both school counselors and subject teachers collaborated and provided services which were based on religious teachings, and 3) the collaboration increased public trust to school and resulted better counsellor performance. In conclusion, the guidance and counseling services at the school run well due to the collaboration between counsellors and stakeholders, not to mention the strategic counseling.